SISTEM INFORMASI PERSEDIAAN OBAT MENGGUNAKAN METODE FEFO BERBASIS MULTI USER DI APOTIK ASSYFA FARMA - Kasih Purwantini; Vivi Kumalasari (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
Inventory is a current asset that has a major role in the accounting cycle. Assyfa Farma Pharmacy is the business of an individual-owned dispensary that is developing in Mranggen District, Demak Regency. The problem faced by Assyfa Farma Pharmacy is that there is no minimum stock of goods because there is no warning that the stock will run out. The number of products that are almost entering the expiration date are on shelves and insecure data storage so that they have a very large risk of data being lost because it is stolen by irresponsible parties. This system will alert the user to the remaining stock of existing goods and the expiration date of the goods. The security of inventory processing data will be guaranteed with a password for users so that anyone cannot access the database. This inventory information system will be built with Microsoft Visual Basic 6.0 programming language, Microsoft SQL Server 2000 as database and multi user network using FEFO method as goods storage method.